Table of Content - - (Journal of Risk and Crisis Management, 2025)
Table of Content: 1. The Impact of the National Strategy for Cybersecurity in Reducing the Risks of Accounting Information Systems - An Empirical Study on thy Saudi Governmental Sector Ms. Nahed Abdullah Barasheed , Dr. Rawya Reda Obaid 2. The Role of Leadership in Managing Risk to Ensure Project Success in the Arabian American Oil Company (Aramco) In Saudi Arabia from 2020 to 2024 Mr. Badr Rashad Qablawi, Ms. Rawda Ayman Abuttahir